Towards Human Rights Equality: The Islamic State's Response to the Syrian Child Refugee Crisis - Deala Rosyida Petriani (Program Studi Hukum Universitas Nusa Putra, 2024)
This research aims to address the critical question of human rights equality for Syrian refugee children. The main focus involves assessing the adaptation and integration of national laws with the Convention on the Rights of the Child, with an emphasis on crucial aspects such as education, age of marriage, child labor, and child nutrition. Through a multidimensional approach, the research findings show the importance of active commitment from the government to draft laws that are aligned with the convention's standards. This integration provides the foundation to tackle crucial issues affecting refugee children, including their right to proper education, combating early marriage, protecting against unsafe child labor, and ensuring adequate nutrition. In addition, the research highlights the urgent need to provide human rights education and training to the entire community, creating a deep awareness of the rights of refugee children. Regional cooperation between member states of the Organization of Islamic Cooperation (OIC) and international cooperation with agencies such as the UN, UNHCR, CRC, ILO, and others, were found to be key to addressing these challenges. The results confirm that only through concerted efforts, strong legal commitments, and a holistic approach, can we achieve optimal human rights equality for Syrian refugee children. The research also highlights the urgency of raising public awareness through campaigns as an essential step in ensuring the protection and fulfillment of refugee children's rights. The conclusion of this article reflects the profound need for collective action to realize equality and justice for Syrian refugee children in an increasingly global context.